THE FORMATION OF URBAN CULTURE IN THE KESH-SHAHRISABZ OASIS AND THE STAGES OF ITS HISTORICAL DEVELOPMENT (International Conference on Education, Psychology and Humanities, 2026)
This thesis analyzes the formation of the Kesh-Shahrisabz oasis as an ancient city and the scholarly debates concerning the location of its historical center, drawing on data from archaeological excavations and numismatic materials. Through the integration of written and material sources, it illuminates the stages of the oasis's historical development, spanning at least 2,700 years.
Keywords: Kesh, Shahrisabz, Kitob, Sogd (Sughd), Nautaka, Gava Suguda, Balandtepa (Zindontepa), archaeological monument, numismatics, urban culture.